2019 Labour History Review Essay Prize Winner: Navigating Deindustrialization in 1970s Britain: The Closure of Bilston Steel Works and the Politics of Work, Place, and Belonging1. Issue 3 (1st December 2020) - Beebee, Matt
Abstract : This article examines the impact of industrial decline on popular constructions of selfhood and place during the 1970s through a case study of the Bilston Steel Works in the West Midlands, which closed in May 1979. Following recent work exploring deindustrialization as a process of transformation, rather than simply a discreet event that is reacted to after the moment of closure, the article makes use of the contemporary accounts of local television and print media to uncover the immediacy of deindustrialization as a disruptive force. While studies of deindustrialization have long identified nostalgia as a characteristic, identity-defining trope of retrospective testimonies, the approach taken in this article suggests that the nostalgic reworking of identity was already a prominent feature of everyday language in late 1970s Bilston. Long-term processes of regional economic restructuring had already begun to recast the personal politics of place. The Bilston Steel Works was the last bastion of the once dominant steel industry in the West Midlands, a feature that Bilston's steelworkers celebrated as a mark of uniqueness and pride at both an individual and community level. A consequence of the closure of the steelworks was its far-reaching social and cultural impact, with the implications for self and place complexly intertwined. The article argues that notions of community and belonging did not necessarily wane but were rather reconstructed and adapted to make sense of, and begin the process of navigating through, industrial decline.